Ethnomedicinal Exploration of Medicinal Plant in Cihanjuang Village, Pandeglang-Banten for Curing Stomacache - Rahmadini, Nuriza; Rindita; Prakasa, Ade Putra; Nugroho, Agung (Media Konservasi, 2022)
Biodiversity in Indonesia is the second highest in the world, the medicinal plants are included in it that must be preserved because of their great benefits for a human being life. Ethnomedicine exploration is a bright way that can be done to record and preserve the biodiversity of medicinal plants in Indonesia. The society in Cihanjuang Village still use medicinal plants to treat digestive disorders, but the lack of documentation will eliminate this knowledge in the future. This ethnomedicine study aims to determine plants which used as diarrhea and ulcer drugs in Cihanjuang Village, consisting of the name, the plant part used, the research method used, and identification of the secondary metabolites. The research methodology used are interview methods with questionnaires, observation, documentation, calculation of Use Value (UV) analysis and phytochemical screening. The informant selection technique used purposive and snowball sampling. The result of this study was the discovery of 24 species of medicinal plants to treat digestive disorders in Cihanjuang Village, most of which belonged to the family of Zingiberaceae and the leaves were the most widely used. The highest of UV’s value for diarrhea is Salak plants (Salacca zalacca) and for ulcers is Hanjuang (Dracaena sanderiana). Some of the species tested for phytochemical screening showed various secondary metabolites that were efficacious in treating digestive disorders. Areuy tulungpung is one of the species that can be studied further due to lack of information as a medicinal plant for digestive disorders.